ADVERSE EFFECT OF MACULAR INTRARETINAL HEMORRHAGE ON THE PROGNOSIS OF SUBMACULAR HEMORRHAGE DUE TO RETINAL ARTERIAL MACROANEURYSM RUPTURE. Issue 5 (May 2020) - Doi, Shinichiro; Kimura, Shuhei; Morizane, Yuki; Hosokawa, Mio M.; Shiode, Yusuke; Hirano, Masayuki; Toshima, Shinji; Takahashi, Kosuke; Hosogi, Mika; Fujiwara, Atsushi; Okanouchi, Toshio; Inoue, Yasushi; et al.
Abstract : Purpose: To investigate the clinical course of submacular hemorrhage associated with ruptured retinal arterial macroaneurysm using swept-source optical coherence tomography. Methods: This study included 23 eyes of 23 consecutive patients diagnosed with submacular hemorrhage associated with ruptured retinal arterial macroaneurysm. Cases underwent displacement of submacular hemorrhage (vitrectomy + subretinal injection of tissue plasminogen activator + air tamponade) and were followed up for 6 months after surgery. Localization of the preoperative hemorrhage and its effect on preoperative and postoperative best-corrected visual acuity, central retinal thickness, and continuity of the ellipsoid zone were measured. Results: Macular intraretinal hemorrhage (IRH) was observed in 17 eyes (73.9%, IRH [+] group) and was not observed in 6 eyes (26.1%, IRH [−] group). The IRH (+) group showed worse postoperative best-corrected visual acuity values compared with the IRH (−) group (0.89 ± 0.47 in logarithm of the minimal angle of resolution units, Snellen equivalent 20/155 and 0.16 ± 0.23, 20/29, respectively; P < 0.01), smaller central retinal thickness values (97.7 ± 53.5 μ m, 173.0 ± 32.3 μ m, respectively; P < 0.01), and a higher rate of ellipsoid zone disruption (100%, 33.3%, respectively; P < 0.01). Conclusion: Patients with preoperative macular IRH showed lower postoperative visual acuity and worse macular contour after submacular hemorrhage displacement compared with patients without macular IRH. Abstract : We investigated the clinical course of displacement of submacular hemorrhage due to ruptured retinal arterial macroaneurysm using swept-source optical coherence tomography and found that preoperative macular intraretinal hemorrhage is a novel poor prognostic factor for submacular hemorrhage displacement.